Gut dysfunction in patients with multiple sclerosis and the role of spinal cord involvement in the disease - Preziosi, Giuseppe (Lippincott Williams And Wilkins, 2013)
OBJECTIVES: Bowel and bladder symptoms are highly prevalent in patients with multiple sclerosis (MS). Bladder dysfunction (affecting 75% of these patients) is caused by disease in the spinal cord, whilst the pathophysiology of bowel dysfunction is unknown. Pathways regulating both the organs lie in close proximity to the spinal cord, and coexistence of their dysfunction might be the result of a common pathophysiology. If so, the prevalence of bladder symptoms should be greater in patients with MS and bowel symptoms. This hypothesis is tested in the study. We also evaluated how patient-reported symptoms quantify bowel dysfunction. PATIENTS AND METHODS: The Neurogenic Bowel Dysfunction questionnaire and the presence of bladder symptoms were recorded in 71 patients with MS and bowel symptoms. Disability, a surrogate clinical measure of spinal cord disease, was assessed using the Expanded Disability Status Scale. Bowel and bladder symptoms were quantified by patient-reported frequency, expressed in time percentage (0, 25, 50, 75 or 100% of the time the symptom was perceived), and patient-reported severity on a visual analogue scale between 0 and 100. RESULTS: The prevalence of bladder symptoms was 85%, which is higher than that expected in an unselected population of patients with MS. Neurogenic Bowel Dysfunction score was significantly correlated with both patient-reported frequency (r=0.860, P<0.0001) and severity of bowel symptoms (r=0.659, P=<0.0001), as well as with the Expanded Disability Status Scale (r=0.526, P<0.0001). CONCLUSION: Our findings suggest that gut dysfunction in patients with MS is secondary to spinal cord disease. Patient-reported bowel symptoms quantify bowel dysfunction well.